Factors Affecting Melon Farmers’ Knowledge Sources and Their Attitudes Towards Input Use; The Case of Hatay Province - Aybüke Kaya (Turkish Journal of Agriculture: Food Science and Technology)
The aim of study is to reveal the factors affecting the knowledge sources used by melon farmers in Hatay province, and their attitudes towards input use. In addition, the research also investigated farmers’ attitudes towards plant protection knowledge and support policies. In the study was surveyed with melon farmers. The data were obtained through face to face interviews during the period of Summer-2022. In the study, factor analysis was used to determine farmers’ the factors affecting the knowledge sources. Factors affecting the knowledge sources used by farmers were determined as two-way and one-way communication. The factors affecting the sources that farmers depend on in dose adjustment were determined as internal and external factors. Besides, farmers think that the knowledge sources should be understandable and accessible. On the other hand, farmers think that the sources they depend on should be accurate and reliable. In melon cultivation, chemicals are used excessively to combat diseases and pests. Also, farmers stated that if precautions are not taken while spraying, poisoning may occur. Moreover, it is thought that empty pesticide containers should be destroyed and excessive use of fertilizers and pesticides may harm products and the environment. Furthermore, farmers claimed that support policies for melon production were not sufficient. As a result, it has been understood that melon farmers have a good level of education and are conscious individuals. However, it is thought that the training and extension activities will help farmers increase their income and environmental awareness.